Γεωμετρική τεκμηρίωση Ι.Μ. Αγίου Ηρακλειδίου με τη χρήση επίγειου σαρωτή λέιζερ - Χριστοδούλου, Μαρία (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
It is obvious, that the thorough study of monuments is an obligation of our era. During the very recent decades, international bodies and related agencies have passed resolutions concerning the obligation for protection, conservation and restoration of monuments. The geometric documentation records the present of monuments, as they have been shaped in the course of time. The geometric documentation provides the necessary background for the studies of the past, as well as the plans for the future. Therefore, it may be defined as the action of acquiring, processing, presenting and recording the necessary data for the determination of the position and the actual existing form, shape and size of a monument in the three dimensional space at a particular moment in time. The geometric recording of a monument is only one, but essential part of the general documentation process dealing with cultural heritage. After the acquisition and development steps, the results are a series of products, usually at large scales, which fully document the geometrical properties of the monument in 2D and in 3D (Georgopoulos et al, 2005). This Thesis Study develops a methodology which can be used for the geometric documentation of monuments. The methodology developed includes the use of geodetic instruments, as well as the use of specialized software in order to extract the final derivatives which can be used for documentation of monuments. The final products were created in 1:50 scale including three vertical sections and six horizontal. These products in late stage were evaluated for their credibility. The objective of this thesis study is the complete geometric documentation of the tomb of St. Irakleidios village Politiko in the Nicosia district.
Keywords: Study of monuments; Protection; Conservation; Restoration; Geometric documentation; Three dimensional (3D); Geometric recording; Cultural heritage; 2D; Documentation of monuments; Μελέτη μνημείων; Προστασία; Διατήρηση; Αποκατάσταση; Γεωμετρική τεκμηρίωση; Γεωμετρική αποτύπωση; Πολιτιστική κληρονομιά; Δισδιάστατη προβολή; Τρισδιάστατη προβολή; Τεκμηρίωση μνημείων